2003
DOI: 10.1208/ps050103
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake and concentrations of tamoxifen upon administration in poly(ε-caprolactone) nanoparticles

Abstract: INTRODUCTIONPurpose: In an attempt to increase the local concentration of tamoxifen in estrogen receptor positive breast cancer cells, we have prepared and characterized poly(İ-caprolactone) (PCL) nanoparticle formulation. Methods: PCL (mol wt 14,800 daltons) nanoparticles were prepared by the solvent displacement method in acetonewater system in the presence of Pluronic F-68. PCL nanoparticles, labeled with rhodamine123, were incubated with MCF-7 estrogen receptor positive breast cancer cells to determine upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 14 publications
1
47
0
Order By: Relevance
“…Thus, TAM arrests the cell cycle in the G1 phase, thereby decreasing cell proliferation [27] and promoting apoptosis. [9] The estrogen receptor-mediated antiestrogenic effect of TAM on breast cancers could lead to either cytostatic or cytotoxic effects. This effect of TAM is concentration dependent.…”
Section: Cell Cycle Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, TAM arrests the cell cycle in the G1 phase, thereby decreasing cell proliferation [27] and promoting apoptosis. [9] The estrogen receptor-mediated antiestrogenic effect of TAM on breast cancers could lead to either cytostatic or cytotoxic effects. This effect of TAM is concentration dependent.…”
Section: Cell Cycle Distributionmentioning
confidence: 99%
“…On the basis of these results, it can be concluded that while TAM governs the morphological changes of the cells and exert in vitro cytostatic activity. Its cytotoxic effect is evident only when the drug is applied in the free form for at least after 48 and 72 h. According to Chawla and Amiji, [9] TAM blocks the cell cycle in the G1 phase, thereby decreasing cell proliferation and increasing apoptosis. This finding is also reflected in this study.…”
Section: Cell Cycle Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, an array of drug delivery systems has been developed using PCL (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…A significant fraction of the administered rhodamine123-loaded poly(e-caprolactone) nanoparticles was found in the perinuclear region of the MCF-7 cells, where estrogen receptors are also localized, after 1 h of incubation. These nanoparticles were rapidly internalized in MCF-7 cells and intracellular tamoxifen concentrations followed a saturable process [93]. In another study, the biodistribution profile of tamoxifen encapsulated in polymeric nanoparticulate formulations after intravenous administration was evaluated, with or without surface-stabilizing agents.…”
Section: Antiestrogensmentioning
confidence: 99%